2021
DOI: 10.3390/cells10081897
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Alveolar Edema in COVID-19

Abstract: The coronavirus disease 2019 (COVID-19) has spread over the world for more than one year. COVID-19 often develops life-threateninghypoxemia. Endothelial injury caused by the viral infection leads to intravascular coagulation and ventilation–perfusion mismatch. However, besides above pathogenic mechanisms, the role of alveolar edema in the disease progression has not been discussed comprehensively. Since the exudation of pulmonary edema fluid was extremely serious in COVID-19 patients, we bring out a hypothesis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 106 publications
0
23
0
Order By: Relevance
“…This causes cytotoxic effects to the host cell and the production of local cytokines and chemokines. Secretion of these cytokines from damaged cells eventually leads to the activation of the immune response to inhibit the viral infection [9] , [10] . Studies have shown that dysregulation of the immune response and disruption of the auto-regulatory immune mechanisms play an important role in the worsening of pulmonary damage in COVID-19 (11) .…”
Section: Introductionmentioning
confidence: 99%
“…This causes cytotoxic effects to the host cell and the production of local cytokines and chemokines. Secretion of these cytokines from damaged cells eventually leads to the activation of the immune response to inhibit the viral infection [9] , [10] . Studies have shown that dysregulation of the immune response and disruption of the auto-regulatory immune mechanisms play an important role in the worsening of pulmonary damage in COVID-19 (11) .…”
Section: Introductionmentioning
confidence: 99%
“…Epithelial cells of the oral cavity, nasal duct, and upper airway are the primary targets for SARS-CoV-2 [ 1 , 2 , 3 ], by the interaction of the viral spike protein (S-protein) with the human angiotensin converting enzyme 2 (ACE2) and other host proteins and glycosaminoglycans [ 4 , 5 ]. Moreover, a recent study defined the susceptibility to SARS-CoV-2 infection as the result of a combination between the genetic variations of SARS-CoV-2 and the genetics of the host [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence indicates a link between silent hypoxemia and the thrombi formation within the CV system and pulmonary vasculature [20]. Increased thrombogenesis and vascular inflammation could lead to severe hypoxemia and subsequent CAD and CV deaths in various populations [5,14,[21][22][23]. A recent study specifically states that the lectin-like oxidized lowdensity lipoprotein receptor-1 (LOX-1) and the potent vasoconstrictor endothelin-1 (ET-1) are intricately involved in atherosclerotic plaques formation and assisting in detecting the CV risk in OSA subjects, respectively [24].…”
Section: Discussionmentioning
confidence: 99%